Procalcitonin and MR-Proadrenomedullin Combination with SOFA and qSOFA Scores for Sepsis Diagnosis and Prognosis: A Diagnostic Algorithm. Issue 1 (July 2018) - Spoto, Silvia; Cella, Eleonora; de Cesaris, Marina; Locorriere, Luciana; Mazzaroppi, Silvia; Nobile, Edoardo; Lanotte, Arcangela M.; Pedicino, Lucia; Fogolari, Marta; Costantino, Sebastiano; Dicuonzo, Giordano; Ciccozzi, Massimo; et al.
ABSTRACT: Purpose: The third Consensus Definitions for Sepsis and Septic Shock (Sepsis-3) defined sepsis as an organ dysfunction consequent to infection. A Sequential Organ Failure Assessment (SOFA) score at least 2 identifies sepsis. In this study, procalcitonin (PCT) and midregional pro-adrenomedullin (MR-proADM) were evaluated along with SOFA and quick SOFA (qSOFA) scores in patients with sepsis or septic shock. Methods: A total of 109 septic patients and 50 patients with noninfectious disease admitted at the Department of Internal Medicine and General Surgery of the University Hospital Campus Bio-Medico of Rome were enrolled. PCT and MR-proADM were measured with immunoluminometric assays (Brahms, Hennigsdorf, Germany). Data were analyzed with receiver-operating characteristic (ROC) curve analysis, likelihood ratios, and Mann–Whitney U test using MedCalc 11.6.1.0 package. Results: At ROC curve analysis, PCT showed the highest area under the curve and positive likelihood ratio values of 27.42 in sepsis and 43.62 in septic shock. MR-proADM and SOFA score showed a comparable performance. In septic shock, lactate showed the most accurate diagnostic ability. In sepsis, the best combination was PCT with MR-proADM with a posttest probability of 0.988. Based upon these results, an algorithm for sepsis and septic shock diagnosis has been developed. MR-proADM, SOFA, and qSOFA scores significantly discriminated survivors from nonsurvivors. Conclusions: PCT and MR-proADM test combination represent a good tool in sepsis diagnosis and prognosis suggesting their inclusion in the diagnostic algorithm besides SOFA and qSOFA scores. Furthermore, MR-proADM as marker of organ dysfunction, with a turn around time of about 30 min, has the advantage to be more objective and rapid than SOFA score.